Hollow carbon nanotube catalyst, preparation method thereof, battery and electric device
Through a safe and simple preparation method, the hollow carbon nanotube catalyst is formed using materials such as polyethylene glycol and zinc nitrate hexahydrate, which solves the danger and complexity of high temperature and high pressure and pickling steps in the prior art, and realizes the preparation of high-activity and high purity catalysts.
Patent Information
- Application Number
- CN202411511903.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-03-21
AI Technical Summary
In the prior art, there is a risk of high temperature and high pressure and explosive gases during the preparation of nitrogen-doped carbon nanotubes, and the steps of acid washing to remove impurities are strictly required for conditions, which easily destroys the crystal structure of the carbon nanotubes.
By mixing polyethylene glycol and zinc nitrate hexahydrate, adjusting the pH to 10, stirring for 12 hours, obtaining a small-sized zinc oxide raw material, and then reacting with 2-methylimidazole in N,N-dimethylformamide solution to form zinc oxide attached to ZIF-8, and calcining at high temperature under nitrogen or argon atmosphere to obtain a hollow carbon nanotube catalyst.
It realizes the safe and simple preparation of high-active and high-purity hollow carbon nanotube catalysts, which reduces the pyrolysis temperature of the material, avoids the pickling step, and improves the product collection amount and catalytic activity.
Smart Images

Figure CN119674100A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of oxygen reduction electrocatalysts, and in particular to a hollow carbon nanotube catalyst and a preparation method thereof, as well as a battery and an electrical device. Background Art
[0002] The development of low-cost, highly stable, and highly catalytically active non-precious metal catalysts for redox reactions (ORR) is crucial for the application of fuel cells and metal-air batteries. Carbon-based catalysts are the preferred choice of non-precious metal catalysts, among which carbon nanotubes have large specific surface area, high conductivity, and excellent electrocatalytic activity, and have been used in commercial applications.
[0003] Nitrogen-doped carbon is the most common method for improving the performance of carbon-based catalytic materials. In the synthesis process of nitrogen-doped carbon nanotubes, not only is it in a high temperature and high pressure environment, but it is also accompanied by the participation of explosive gases such as hydrogen and methane. At the end of the carbon nanotube preparation process, most of them will use an acid pickling step to remove impurities. There are strict requirements for the control of acid concentration, dosage, pickling time and other conditions. Improper control can easily destroy the crystal structure of carbon nanotubes. Therefore, the dangers of high temperature and high pressure, explosive gas, and strong acid treatment in the existing preparation technology are issues that need to be developed and improved. Summary of the invention
[0004] In view of this, the purpose of the present application is to provide a hollow carbon nanotube catalyst and a preparation method thereof, so that the preparation method can safely and simply prepare a hollow carbon nanotube with high ORR activity and purity;
[0005] Another object of the present application is to provide a battery and an electrical device based on the hollow carbon nanotubes.
[0006] In order to solve the above technical problems / achieve the above objectives or at least partially solve the above technical problems / achieve the above objectives, as a first aspect of the present application, a method for preparing a hollow carbon nanotube catalyst is provided, comprising:
[0007] Polyethylene glycol and zinc nitrate hexahydrate are mixed, the pH value is adjusted to 10, and stirred at a constant temperature of 80° C. for 12 h to obtain a small-diameter zinc oxide raw material;
[0008] 2-methylimidazole reacts with the small-diameter zinc oxide raw material in an N,N-dimethylformamide solution to obtain zinc oxide attached to ZIF-8;
[0009] The zinc oxide attached to the ZIF-8 is calcined at high temperature in a nitrogen and / or argon atmosphere to obtain a hollow carbon nanotube catalyst.
[0010] Optionally, the high temperature calcination includes heating to 800±20°C and maintaining for 3-7 hours. Further optionally, the high temperature calcination includes first heating to 200±20°C and maintaining for 1-5 hours, and then heating to 800±20°C and maintaining for 3-7 hours.
[0011] Optionally, the mass ratio of the polyethylene glycol to zinc nitrate hexahydrate is 0.9:3, and the mass volume ratio of the small-diameter zinc oxide raw material, 2-methylimidazole and N,N-dimethylformamide is 0.84 g:6.6 g:480 mL.
[0012] Optionally, ammonia water is used to adjust the pH value in the preparation method.
[0013] As a second aspect of the present application, a hollow carbon nanotube catalyst prepared by the preparation method is provided.
[0014] As a third aspect of the present application, a composite catalyst is provided, which uses the hollow carbon nanotube catalyst described in the present application as a carrier and loads one or more active ingredients selected from metal oxides and / or precious metals.
[0015] As a fourth aspect of the present application, a battery is provided, wherein the negative electrode thereof includes the hollow carbon nanotube catalyst described in the present application.
[0016] Optionally, the battery comprises a metal-air battery and a fuel cell.
[0017] As a fifth aspect of the present application, an electrical device is provided, comprising the battery described in the present application, wherein the battery provides electrical energy for the electrical device.
[0018] This application uses a diameter control strategy with reaction time as a variable, uses an easily reproducible water bath synthesis method to make zinc oxide nanomaterials of different diameters as templates and attaches ZIF-8, and the obtained small-diameter zinc oxide nanotubes are more easily carbonized completely, and zinc ions are volatilized to obtain hollow carbon nanostructures, presenting a layered network structure with high porosity, high flux and high purity. The preparation method described in this application clarifies the reaction conditions, reduces the step of pickling to remove impurities, and thus increases the amount of product collected, and while reducing the material pyrolysis temperature, it also ensures the catalytic activity of the carbon-based catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application.
[0020] Figure 1 Shown is the microstructure of the hollow carbon nanotube ZIF8 / ZnO-12 prepared in Example 1 of the present application;
[0021] Figure 2 Shown is a high-power transmission electron microscopy image of the hollow carbon nanotube ZIF8 / ZnO-12 prepared in Example 1 of the present application;
[0022] Figure 3 Shown are the XRD patterns of the samples prepared in Example 1 and Comparative Examples 1 and 2 of the present application;
[0023] Figure 4 Shown are the ORR linear sweep voltammetric curves of the samples prepared in Example 1 and Comparative Examples 1 and 2 of the present application at a rotation speed of 1600 rpm;
[0024] Figure 5 Shown are the ORR linear sweep voltammetry curves of the sample prepared in Example 1 of the present application at different rotation rates. DETAILED DESCRIPTION
[0025] The present application discloses a hollow carbon nanotube catalyst and a preparation method thereof, as well as a battery and an electrical device. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all deemed to be included in this application. The products, processes and applications described in this application have been described through preferred embodiments. Relevant personnel can obviously modify or appropriately change and combine the products, processes and applications described in this article without departing from the content, spirit and scope of this application to realize and apply the technology of this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0026] It should be noted that, in this article, if relational terms such as "first" and "second", "step 1" and "step 2", and "(1)" and "(2)" appear, they are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "comprise", "include" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or equipment including the elements. At the same time, the embodiments in this application and the features in the embodiments may be combined with each other without conflict.
[0027] In a first aspect of the present application, a method for preparing a hollow carbon nanotube catalyst is provided, comprising:
[0028] Polyethylene glycol and zinc nitrate hexahydrate are mixed, the pH value is adjusted to 10, and stirred at a constant temperature of 80° C. for 12 h to obtain a small-diameter zinc oxide raw material;
[0029] 2-methylimidazole reacts with the small-diameter zinc oxide raw material in an N,N-dimethylformamide solution to obtain zinc oxide attached to ZIF-8;
[0030] The zinc oxide attached to the ZIF-8 is calcined at high temperature in a nitrogen and / or argon atmosphere to obtain a hollow carbon nanotube catalyst.
[0031] The present application uses a water bath synthesis method that is easy to reproduce to prepare a small-diameter zinc oxide nanomaterial. The key to the step is to clarify the time, pH value and temperature of heating and stirring. The different stirring times make the diameter of zinc oxide significantly different. If the time is too short, the zinc oxide structure is a nano flower-like structure. Even in the process of subsequent ZIF-8 attachment and carbonization, the structural performance is only the nano flower-like structure scattered, and zinc oxide will not volatilize at high temperature, and the prepared carbon nanotube purity is not high. And the stirring time is too long, and the structure of zinc oxide is a mixture of incomplete hollow nanotubes and relatively complete nanotubes. Due to the uneven structure, the result of subsequent ZIF-8 attachment and carbonization will also appear incomplete volatilization of zinc oxide. Therefore, the present application clarifies the reaction conditions, first controls the tubular structure of the template zinc oxide, and after attachment to ZIF-8 and carbonization, the nanotubes will be completely carbonized, and the zinc ions will volatilize to obtain a carbon nano hollow structure with higher purity. In the subsequent further processing, the step of removing impurities by pickling can be subtracted, thereby increasing the collection amount of the product and improving the yield.
[0032] At the same time, the zinc oxide structures obtained at different stirring times, after the same ZIF-8 attachment and carbonization temperature conditions, the zinc oxide with uniform structure and small diameter in the present application is preferentially carbonized completely at 800°C, while the comparative sample requires a higher pyrolysis temperature, that is, the volatilization temperature of zinc oxide must reach 907°C to achieve the effect of removing impurities. The present application is based on the relationship between activation energy and particle size, that is, the activation energy of thermal decomposition decreases as the particle size decreases, and the apparent activation energy is linearly related to the inverse of the particle size. The pyrolysis temperature cost required for the reaction is reduced, the reaction energy loss is saved, and the production efficiency is improved.
[0033] In certain embodiments of the present application, the high temperature calcination includes heating to 800±20°C and maintaining for 3-7h. In other embodiments of the present application, in order to avoid the collapse of the material structure caused by too fast a heating rate, the present application adopts a two-stage heating method for high temperature calcination, and the temperature is maintained at about 200°C for a period of time in the middle to maintain the stability of the structure. Specifically, the high temperature calcination includes first heating to 200±20°C and maintaining for 1-5h, and then heating to 800±20°C and maintaining for 3-7h. The heating rate can be selected as 5°C / min.
[0034] In certain embodiments of the present application, the mass ratio of polyethylene glycol and zinc nitrate hexahydrate is 0.9:3, and the mass volume ratio of the zinc oxide raw material, 2-methylimidazole and N, N-dimethylformamide is 0.84g:6.6g:480mL. Among them, polyethylene glycol guides the formation of zinc oxide structure as a soft template, and polyethylene glycol has good water solubility, which can reduce the surface tension of zinc oxide and contribute to the stability of zinc oxide in solution. As for N, N-dimethylformamide, on the one hand, it acts as a reaction solvent, can dissolve zinc oxide and 2-methylimidazole, so that they are evenly dispersed in the solution in the form of molecules or ions, and provide necessary conditions for subsequent coordination reactions; on the other hand, it can also promote the coordination reaction. Under heating conditions, the presence of N, N-dimethylformamide contributes to the full contact and reaction between the reactants, thereby accelerating the coordination reaction. In addition, the concentration of N, N-dimethylformamide can affect the particle size and morphology of the generated ZIF-8. For example, at a higher concentration of N,N-dimethylformamide, the collision frequency between reactants increases, which may promote the formation and growth of crystal nuclei, thereby obtaining ZIF-8 with a larger particle size. At the same time, the polarity and molecular structure of the N,N-dimethylformamide solvent also determine the crystallinity and porosity of ZIF-8. The appropriate conditions in this application are conducive to the formation of highly crystalline and highly porous ZIF-8 materials.
[0035] In the second aspect of the present application, a hollow carbon nanotube catalyst prepared by the preparation method is provided, which has a uniform structure, a hollow tube, a layered network structure at a microscopic level, a tube diameter of 200-300nm, and is attached with hexahedral ZIF-8. The hollow carbon nanotubes described in the present application have excellent oxygen reduction catalytic activity, and the layered network structure presented, the larger specific surface area, and the better porosity are conducive to the transport of ions and the catalytic reaction, and can be further applied in the fields related to electrocatalyst carriers, photocatalyst carriers, fuel cells, and metal-air batteries.
[0036] In the third aspect of the present application, a composite catalyst is provided, which uses the hollow carbon nanotube catalyst described in the present application as a carrier and loads one or more active ingredients selected from metal oxides and / or precious metals, such as titanium dioxide. This composite catalyst can be applied to the fields of electrocatalysis, photocatalysis, wastewater treatment, sewage treatment, etc. For example, in the field of photocatalysis, hollow carbon nanotubes can also be used as a carrier to improve the catalytic efficiency and stability of the photocatalyst. For example: TiO 2 Nanoparticles are loaded on hollow carbon nanotubes to form TiO 2 / CNTs composite. In the photocatalytic reaction, due to the presence of carbon nanotubes, this composite can effectively prevent the agglomeration of nanoparticles and improve the transmission efficiency of electrons, thereby significantly improving the photocatalytic efficiency. In wastewater treatment, this composite catalyst can degrade organic pollutants in wastewater and purify wastewater. In the field of sewage treatment, this composite catalyst converts harmful substances in sewage into harmless substances through catalytic oxidation, reduction and other reactions, thereby achieving deep purification of sewage.
[0037] In a fourth aspect of the present application, a battery is provided, wherein a negative electrode thereof includes the hollow carbon nanotube catalyst described in the present application.
[0038] In certain embodiments of the present application, the battery includes a metal-air battery and a fuel cell. In other embodiments of the present application, a zinc-air battery is provided, the core components of which include a zinc foil anode, an electrolyte (preferably a 6.0M KOH aqueous solution) and a cathode (a waterproof and breathable carbon cloth coated with a hollow carbon nanotube catalyst of the present application).
[0039] In the fifth aspect of the present application, there is provided an electrical device, comprising the battery described in the present application, wherein the battery provides electrical energy for the electrical device.
[0040] In each group of comparative experiments provided in this application, unless otherwise specified, other experimental conditions, materials, etc. are kept consistent except for the differences indicated in each group, so as to provide comparability. The experimental materials and reagents used in the examples can be obtained from commercial channels unless otherwise specified.
[0041] The following is a further description of a hollow carbon nanotube catalyst and a preparation method thereof, as well as a battery and an electrical device provided in the present application.
[0042] Embodiment 1:
[0043] Zinc oxide was prepared in the following manner:
[0044] Weigh 0.9g of polyethylene glycol 2000 and 3g of zinc nitrate hexahydrate and add them to 375mL of deionized water, mix and stir at room temperature for 15min. Place the mixed solution in an ultrasonic cleaner and add 1M ammonia water dropwise until the pH is 10. Repeat the above method to obtain three groups of mixed solutions, and then place them in three thermostatically heated magnetic stirrers, set the water bath temperature to 80℃, and stir for 12h. After filtering the obtained precipitate, wash it with deionized water and anhydrous ethanol for 3 times respectively to remove PEG residues and nitrate ions. Finally, place the sample in a vacuum drying oven and dry it at 60℃ for 12h to obtain a product recorded as ZnO-12.
[0045] ZIF-8 attached with zinc oxide was prepared in the following manner:
[0046] A mixture of 160 mL of deionized water and 480 mL of N,N-dimethylformamide was stirred and dissolved with 6.6 g of 2-methylimidazole. 0.84 g of ZnO-12 was added to the solution and treated in an ultrasonic cleaner for 30 min. The solution was then placed in an electric constant temperature blast drying oven at 60°C for 48 h to obtain zinc oxide attached to ZIF-8.
[0047] Hollow carbon nanotubes are prepared in the following manner:
[0048] The obtained ZIF-8 coated zinc oxide was placed in a crucible and transferred to a vacuum tube furnace. Before carbonization, the air in the furnace was evacuated by blowing nitrogen and the parameters were set. The furnace was heated to 200°C at a rate of 5°C / min and maintained for 2h, and then the temperature was raised to 800°C at the same rate and maintained for 5h. The obtained product was recorded as ZIF8 / ZnO-12.
[0049] The microstructure of the nitrogen-doped hollow carbon nanotubes ZIF8 / ZnO-12 prepared in Example 1 was studied using a scanning electron microscope. Figure 1 As shown in the figure, the hexahedral structure of ZIF8 attached to ZIF8 / ZnO-12 is clearly visible, and the overall layered network structure shows a larger specific surface area. This structure is more conducive to the transport of ions during the catalytic process and improves the catalytic activity.
[0050] Figure 2The internal structure was studied using a high-magnification electron transmission microscope. It can be seen from the figure that the carbon shell left after the carbonization of zinc oxide presents a hollow structure, with almost no residual zinc oxide structure, and the tube diameter is 200-300nm. The presence of attached ZIF8 is the key to the catalytic effect. ZnO attached to porous ZIF-8 to produce nitrogen-rich carbon nanotubes can significantly increase the effective active sites for ORR. These nitrogen-activated carbon nanotubes have been found to have many defects, which are usually found in N-doped graphene materials and produce a large number of active sites to improve electrocatalytic activity.
[0051] Comparative Example 1:
[0052] The difference from Example 1 is that the stirring and heat preservation time for the preparation of zinc oxide is 8 hours, the obtained zinc oxide is marked as ZnO-8, and the finally obtained carbon nanotubes are marked as ZIF8 / ZnO-8.
[0053] Comparative Example 2:
[0054] The difference from the embodiment is that the stirring and heat preservation time for the preparation of zinc oxide is 14 hours, the obtained zinc oxide is marked as ZnO-14, and the finally obtained carbon nanotubes are marked as ZIF8 / ZnO-14.
[0055] Experimental example:
[0056] 1. X-ray diffraction (XRD) determination
[0057] The powder materials ZIF8 / ZnO-12, ZIF8 / ZnO-8, and ZIF8 / ZnO-14 prepared in Example 1 and Comparative Examples 1 and 2 were measured by X-ray diffraction (XRD). The results are as follows: Figure 3The powder is the result of ZnO prepared at different preparation times of 8h, 12h, and 14h after coating and carbonization. By comparing the catalysts (ZIF8 / ZnO-8, ZIF8 / ZnO-14) thermally decomposed after the synthesis of ZIF-8 attached nanomaterials for 8h and 14h, and comparing with the standard card JCPDS (PDF#89-1397), it can be determined that the diffraction angles of 31.74°, 34.38°, 36.21°, 47.48°, 56.53°, 62.76°, 66.30°, 67.87°, 69.00°, and 76.87° correspond to the (100), (002), (101), (102), (110), (103), (200), (112), (201), and (202) crystal planes of ZnO, respectively, and the prepared ZnO nanomaterials belong to the hexagonal wurtzite structure, and their X-ray diffraction patterns show sharp and narrow peaks, all of which show a certain degree of crystallization and the presence of impurities. However, the diffraction peak of ZIF-8 / ZnO-12 near 21° is wide, indicating that the degree of graphitization is low and it is mainly amorphous carbon. It also does not contain any residual ZnO or Zn(OH)2 or other impurity peaks and has a high purity.
[0058] 2. Electrochemical test results
[0059] The test method used is the rotating electrode method, the working electrode is a glassy carbon electrode, the reference electrode is a reversible hydrogen electrode, and the counter electrode is a platinum electrode; wherein the working electrode preparation method is as follows:
[0060] The catalyst was coated on the glassy carbon electrode in the following manner: 10 mg of the catalyst was weighed on an analytical balance and dispersed in 0.15 ml of deionized water and 0.35 ml of ethanol, and then 10 μL of 5 wt% Nafion solution was added thereto and ultrasonically dispersed for 30 min. Then 10 μL of the ink suspension was taken with a pipette and dropped on the newly polished glassy carbon disk electrode, and dried under an infrared lamp to obtain a working electrode.
[0061] The test environment was a 0.1 mol saturated oxygen-permeated potassium hydroxide solution, the rotation speed of the electrode was 400 to 2500 r / min, the scanning range was -0.665 V to 0.335 vs. RHE, and a linear scanning voltammetric curve was obtained.
[0062] Figure 4It is the ORR linear scanning voltammetry curve of Example 1 and Comparative Examples 1 and 2 at a rotation speed of 1600 rpm. It can be seen from the figure that ZIF8 / ZnO-12 shows Eoneset=0.9V, E1 / 2=0.785V, JL=-4.39mA cm-2; ZIF8 / ZnO-8 has Eoneset=0.837V, E1 / 2=0.72V; ZIF8 / ZnO-14 has Eoneset=0.872V, E1 / 2=0.74V. ZIF8 / ZnO-12, as the sample with the highest degree of carbonization, shows excellent ORR activity among carbon materials.
[0063] Figure 5 In order to further evaluate the ORR kinetics of the samples, RRDE related tests were performed. In Example 1, at 400-2500 rpm, the faster the speed, the more O 2 It diffuses to the catalyst surface faster, and the current density increases with the increase of rotation speed, showing extremely excellent ORR activity.
[0064] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A method for preparing a hollow carbon nanotube catalyst, characterized in that: include: Polyethylene glycol and zinc nitrate hexahydrate are mixed, the pH value is adjusted to 10, and stirred at a constant temperature of 80° C. for 12 h to obtain a small-diameter zinc oxide raw material; 2-methylimidazole reacts with the small-diameter zinc oxide raw material in an N,N-dimethylformamide solution to obtain zinc oxide attached to ZIF-8; The zinc oxide attached to the ZIF-8 is calcined at high temperature in a nitrogen and / or argon atmosphere to obtain a hollow carbon nanotube catalyst.
2. The preparation method according to claim 1, characterized in that: The high temperature calcination includes raising the temperature to 800±20° C. and maintaining it for 3-7 hours.
3. The preparation method according to claim 1 or 2, characterized in that: The high temperature calcination includes firstly raising the temperature to 200±20°C and maintaining it for 1-5 hours, and then raising the temperature to 800±20°C and maintaining it for 3-7 hours.
4. The preparation method according to claim 1, characterized in that: The mass ratio of the polyethylene glycol to zinc nitrate hexahydrate is 0.9:3, and the mass volume ratio of the small-diameter zinc oxide raw material, 2-methylimidazole and N,N-dimethylformamide is 0.84 g:6.6 g:480 mL.
5. The preparation method according to claim 1, characterized in that: The pH value was adjusted with aqueous ammonia.
6. The hollow carbon nanotube catalyst prepared by the preparation method according to claims 1-5.
7. A composite catalyst, characterized in that The hollow carbon nanotube catalyst according to any one of claims 1 to 5 is used as a carrier, and one or more active components selected from metal oxides and / or precious metals are loaded.
8. A battery, characterized in that: The negative electrode comprises the hollow carbon nanotube catalyst according to any one of claims 1 to 5.
9. The battery according to claim 8, characterized in that The batteries include metal-air batteries and fuel cells.
10. An electrical device, characterized in that: The battery comprises the battery as claimed in claim 8 or 9, wherein the battery provides electrical energy for the electrical device.